The Maintenance team action on the dampness at residential colleges in Malaysian universities / Siti Nurul Hidayah Omar - Omar, Siti Nurul Hidayah (Faculty of Architecture, Planning and Surveying, 2015)
Dampness is the most popular and main defect to the buildings and about 50% the causes from all defects available. It adversely affects the living conditions of occupiers, cause rapid deterioration on building materials and components, may lead to structural problems, degrade finishes and results in deterioration in furniture, fixtures and fittings in the building. Dampness is a very common problem in both public and private buildings in Malaysia. This study presents the dampness problems that occur around the residential college building in the Malaysian Universities. The purpose of this study was to establish the factors to be considered by the maintenance team in protecting the building from dampness problems. Therefore, this study will look at the extent to which this dampness problems occur in residential buildings colleges and actions that can be applied by the maintenance team to address the problem of dampness in buildings a university college in Malaysia. Actually, this research was conducted on three college buildings in Malaysian Universities and was getting information from the maintenance management department for college building itself that involved in that maintaining work for building college. The three universities in Malaysia are being sampled in order to achieve the aim and objectives of this research are Universiti Putra Malaysia (UPM), Universiti Teknologi Mara (UiTM) and Universiti Kebangsaan Malaysia (UKM). The aim of this research is to establish factor that need to be consider by the maintenance team in preventing dampness in the building, while three objectives for this research is to identify the common dampness in the building, to investigate the causes dampness in the building and to examine maintenance action to prevent dampness in building. For the result, after this research is completed, the results finding obtained to fulfill the objectives of of this research showed that common dampness in the residential college building in Malaysian universities is penetrating damp types. This type damp usually wall in the toilet area. Then, based on data collection, the failure of waterproofing is a major cause of the defect dampness problems that began widely in the college building. This research also found that taking solution as early planning is most program or strategy for maintenance work to prevent the dampness defect which has been as step to overcome the problem of dampness is a good suggestion to prevent a dampness problem in college building in Malaysian universities. Many causes of persistent building dampness can be prevented through careful attention to details in the design, construction, and commissioning phases. Owners, developers and also occupants itself should be aware of the importance of preventing building dampness and the reasons why buildings can become persistently damp.